Development of a Learning Activity Package Based on Carl R. Roger’s Instructional Model for Enhancing Professional Competencies in Safety and Mechanic Tool Use of the 1st Year Vocational Certificate Students, Songkhla Polytechnic College - Nunkaew, Anurak; Makchuchit, Nongnaphat; Boonrat, Arisra (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2022)
This study aimed to develop a learning activity package on safety and use of mechanic tools. The research participants were 31 first-year vocational certificate students from the Department of Automotive Mechanics, Songkhla Polytechnic College, year of 2021. This study intended 1) to develop a learning activity package on safety and use of mechanic tools and determine its efficiency according to the specified criteria E 1 / E 2 = 80 / 80; 2) to measure and compare the learning performance of students before and after teaching with the learning activity package; and 3) to study the satisfaction of students toward the teaching kit. This research utilized a single-group model of student-participants measured before and after treatments using pre-test and post-test designs. Statistics used to analyze data included mean, standard deviation and t-test. The results of this study showed that 1) the efficiency of the teaching kit on safety and use of mechanic tools was higher than the specified criteria of 80/80, obtained an actual efficiency value of 83.01/84.36; 2) the comparison of learning outcomes before and after teaching with the learning activity package revealed that students in the first-year of vocational certificate had significantly higher achievement scores after studying with the learning activity package at 0.01 level; and 3) the students’ satisfaction toward the teaching kit was at the highest level (mean = 4.85).